Therapeutic potential of artemisinin and its derivatives in managing kidney diseases - Jin, Qi; Liu, Tongtong; Chen, Danqian; Yang, Liping; Mao, Huimin; Ma, Fang; Wang, Yuyang; Li, Ping; Zhan, Yongli (Frontiers in Pharmacology, 2023)
Artemisinin, an antimalarial traditional Chinese herb, is isolated from Artemisia annua. L, and has shown fewer side effects. Several pieces of evidence have demonstrated that artemisinin and its derivatives exhibited therapeutic effects on diseases like malaria, cancer, immune disorders, and inflammatory diseases. Additionally, the antimalarial drugs demonstrated antioxidant and anti-inflammatory activities, regulating the immune system and autophagy and modulating glycolipid metabolism properties, suggesting an alternative for managing kidney disease. This review assessed the pharmacological activities of artemisinin. It summarized the critical outcomes and probable mechanism of artemisinins in treating kidney diseases, including inflammatory, oxidative stress, autophagy, mitochondrial homeostasis, endoplasmic reticulum stress, glycolipid metabolism, insulin resistance, diabetic nephropathy, lupus nephritis, membranous nephropathy, IgA nephropathy, and acute kidney injury, suggesting the therapeutic potential of artemisinin and its derivatives in managing kidney diseases, especially the podocyte-associated kidney diseases.